Mendeley: Perpustakaan Digital Pribadi untuk Literatur Ilmiah dan Sahabat Terbaik Peneliti di Era Digital - Angelia Leovita; Yulia Rahmawati Z; Febriani Febriani; Sapta Eka Putra; Dian Fauzi (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
The development of information and communication technology in the digital era has increased access to and productivity of scholarly publications, while also creating challenges in managing academic literature and references. Final-year students, particularly those from non–Information Technology programs, often experience difficulties in organizing references systematically, maintaining citation consistency, and avoiding unintentional plagiarism. This article aims to describe the implementation and outcomes of a community service program that provided training on the use of Mendeley as a personal digital library for managing scholarly literature. The program was conducted over two days using a participatory and hands-on approach involving students from Universitas Tamansiswa in Padang. The training methods included conceptual lectures, live demonstrations, and practical sessions covering Mendeley installation, reference management, automatic citation, and bibliography generation. The results indicate improvements in participants’ understanding and skills in reference management, as well as increased awareness of academic integrity. Overall, the training proved effective in enhancing efficiency and writing quality in the preparation of theses or final projects.